ENVIRONMENTAL PROTECTION — AN IMPORTANT FACTOR FOR PUBLIC HEALTH - Yusupova , Madina (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article examines environmental pollution and its impact on human health, as well as the role of environmental protection measures in strengthening public health. The medical significance of maintaining the hygienic quality of air, water, and soil is analyzed based on scientific sources and statistical data